2017
DOI: 10.1101/206037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic analysis ofde novovariants reveals sex differences in complex and isolated congenital diaphragmatic hernia and indicatesMYRFas a candidate gene

Abstract: Congenital diaphragmatic hernia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…There is some emerging evidence that there may be sex-related differences in the genetics of isolated CDH, with girls carrying more de novo coding variants; however, the correlation between genetic aetiology and CDH severity is as yet unclear 12. The reasons for the higher proportion of girls dying before operative repair of CDH merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…There is some emerging evidence that there may be sex-related differences in the genetics of isolated CDH, with girls carrying more de novo coding variants; however, the correlation between genetic aetiology and CDH severity is as yet unclear 12. The reasons for the higher proportion of girls dying before operative repair of CDH merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent trio studies have reported DNMs in MYRF as candidates in congenital diaphragmatic hernia and congenital heart disease. 54,55 Most of them were damaging missense mutations located in the conserved DBD and ICD. Additionally, MYRF was identified during the course of constructing a transcript map of the region encompassing the BEST1 gene (OMIM 607854) and eye tissue-specific cDNA selection.…”
Section: Discussionmentioning
confidence: 99%
“…Missense variants are the most abundant type of coding genetic variants and a major class of genetic risk in a broad range of common and rare diseases. Previous studies have estimated that there is substantial contribution from de novo missense mutations to structural birth defects [1][2][3][4][5] , and neurodevelopmental disorders [6][7][8] .…”
Section: Main Textmentioning
confidence: 99%